The Influence of Remuneration and Work Discipline on Employee Performance With Work Motivation as Intervening Variables (Case Study at State Islamic Junior High School 2 Jember) - Okta Diantika; Yuslinda Dwi Handini; Wheny Khristianto (Universitas Muhammadiyah Jember Press, 2026)
This research is motivated by the importance of human resources in determining organizational success and the gap in the remuneration system between Civil Servants (PNS) and Government Employees with Work Agreements (PPPK) at MTs Negeri 2 Jember. The differences in allowances and facilities create a sense of injustice that has the potential to reduce employee motivation and performance. The purpose of this study is to analyze the effect of remuneration and work discipline on employee performance with work motivation as an intervening variable. This study uses a quantitative approach with Structural Equation Modeling–Partial Least Square (SEM-PLS) analysis techniques. The results show that remuneration has a positive and significant effect on employee performance (β = 0.243; p = 0.007), work discipline has a positive and significant effect on performance (β = 0.258; p = 0.028), and both have a significant effect on work motivation. Work motivation was also shown to have a positive effect on performance (β = 0.392; p = 0.000), but did not mediate the relationship between remuneration and performance (p = 0.060). These findings indicate that improving employee performance at MTs Negeri 2 Jember can be achieved through a fair remuneration system and consistent implementation of work discipline, while work motivation plays a direct role in strengthening employee quality and productivity.